Acidolysis of phospholipids with medium‐chain fatty acids over M‐SBA‐15 (M = Zn, Al) silicas as efficient solid catalysts. (5th March 2022) - Cheng, Ke; Zhang, Jianghua; Yang, Shasha; Yin, Fawen; Li, Zixuan; Wang, Ting; Zhou, Dayong
Abstract: BACKGROUND: Efficient and sustainable production of structured phospholipids (SPLs) enriched in medium‐chain fatty acids (MCFAs) in a heterogeneous manner is crucial for their potential applications in functional foods and drugs. Herein, for the first time, Zn‐ and Al‐incorporated SBA‐15 silicas were prepared by the coprecipitation method and further researched for catalytic synthesis of MCFA‐enriched SPLs through acidolysis reaction of natural phospholipids with capric or caprylic acid. RESULTS: The as‐prepared Zn‐ and Al‐incorporated SBA‐15 samples exhibited superior catalytic activities under mild experimental conditions (50 °C, 6 h) to commercial homogeneous Lewis acids and benchmark enzymes. Correspondingly, the capric acid and caprylic acid incorporations were respectively achieved up to 40.25 ± 0.40% (or 35.08 ± 0.09%) and 37.26 ± 0.38% (or 33.02 ± 0.13%) for Zn‐ (or Al‐) incorporated SBA‐15 catalyst. Moreover, various methods such as scanning electron microscopy with energy‐dispersive X‐ray spectrometry, ultraviolet–visible diffuse reflectance spectroscopy and pyridine–Fourier transform infrared spectroscopy were utilized to characterize the two catalysts in order to elucidate the possible structure–performance relationship. Accordingly, the above‐mentioned satisfactory results are most probably due to the well‐ordered mesostructures and large amounts of active Lewis acid sites existing in the investigated materials. Noticeably, the two catalysts featured good separation and excellent recyclability as well. CONCLUSION: The Zn‐ and Al‐incorporated SBA‐15 catalysts studied in this work might shed light on novel, sustainable and economic alternatives for effective SPL production to diminish the applications of conventional homogeneous catalysts and biocatalysts in food industries. © 2022 Society of Chemical Industry.